Dynamics of precarity among 'new migrants': exploring the worker–capital relation through mobilities and mobility power. Issue 5 (3rd September 2019) - Vickers, Tom; Clayton, John; Davison, Hilary; Hudson, Lucinda; A Cañadas, Maria; Biddle, Paul; Lilley, Sara
ABSTRACT: This article conceptualises the role of mobilities within precarious working and living conditions, drawing on qualitative analysis of interviews (n = 52) and a policy seminar (n = 50) in North-East England. It focuses on refugees, asylum seekers, and Eastern European EU migrants, as policy-constructed groups that have been identified as disproportionately concentrated in precarious work. The article develops three 'dynamics of precarity', defined as 'surplus', 'rooted', and 'hyper-flexible', to conceptualise distinct ways of moving that represent significant variations in the form that precarity takes. The article concludes that understanding precarity through mobilities can identify points of connection among today's increasingly heterogeneous working class.